2004
DOI: 10.1001/archinte.164.17.1904
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori Eradication on Platelet Recovery in Patients With Chronic Idiopathic Thrombocytopenic Purpura

Abstract: Eradication of H pylori may prove effective in increasing platelet count in H pylori-positive patients with chronic ITP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 18 publications
4
27
2
4
Order By: Relevance
“…We also found a significant increase in platelet count of eight patients during six months of follow-up (P < 0.001) compared with the baseline platelet count. This finding was consistent with the findings of other studies (11,12). In the study of Ferrara et al (11) on 24 patients with CITP, eight individuals (33.3%) were infected with H. pylori and eradication treatment was successfully achieved in six out of eight patients with significant increases in platelet count in all six cases.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We also found a significant increase in platelet count of eight patients during six months of follow-up (P < 0.001) compared with the baseline platelet count. This finding was consistent with the findings of other studies (11,12). In the study of Ferrara et al (11) on 24 patients with CITP, eight individuals (33.3%) were infected with H. pylori and eradication treatment was successfully achieved in six out of eight patients with significant increases in platelet count in all six cases.…”
Section: Discussionsupporting
confidence: 91%
“…Another study by Sato et al in Japan was performed on 53 patients with CITP (12). In this study prevalence of H. pylori infection among CITP patients was 73% (39 patients); eradication of HP in 32 cases led to suitable response in 27 patients (12). Although the above articles are in line with our study, some reports did not show any platelet recovery in the H. pylori treatment group compared to the control group (13,14).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These include acute gastritis [1][2][3] , chronic atrophic gastritis [3,4] , intestinal metaplasia [5] , peptic ulcer [6,7] , mucosal associated lymphoid tissue (MALT) lymphoma [8] , and other disorders [9,10] . Although many epidemiological studies and animal models revealed close association between gastric cancer and H pylori infection [11][12][13] , there have been few studies that report on genetic alterations suggestive of gastric carcinogenesis associated with chronic H pylori infection [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, important studies have demonstrated significant improvement in the platelet count after bacterium eradication in individuals with chronic ITP [32,33] as well as favorable platelet response in the patients in whom H. pylori was successfully eradicated [34,35]. Other important observation is that the absolute number of plasma cytoid dendritic cells, which is generally reduced in patients with ITP, is also reduced in patients with ITP and concomitant H. pylori infection; but it was observed that this number increased in those individuals after bacterium eradication, one important aspect if we consider the possible relationship between the infection and ITP development [36].…”
Section: Helicobacter Pylorimentioning
confidence: 99%